Preparation of conducting polymer composites by solid state polymerization of 2,5-dibromo-3,4-ethylenedioxythiophene - Sabai Kusonsong (Chulalongkorn University, 2013)
Thesis (M.Sc.)--Chulalongkorn University, 2007